China on strike: narratives of worker's resistance - Li, Zhongjin; Friedman, Eli; Ren, Hao (Chicago, 2016)
"China has been the fastest growing major economy in the world for three decades. It is also home to some of the largest, most incendiary, and most underreported labor struggles of our time. "China on Strike," the first English-language book of its kind, provides an intimate and revealing window into the lives of workers organizing in some of China s most profitable factories, which supply Apple, Nike, Hewlett Packard, and other multinational companies. Drawing on dozens of interviews with Chinese workers, this book documents the processes of migration, changing employment relations, worker culture, and other issues related to China s explosive growth."